2008
DOI: 10.1007/s00213-008-1261-1
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activation during delay discounting in abstinent methamphetamine dependent individuals

Abstract: Background-Methamphetamine (MA)-dependent individuals prefer smaller immediate over larger delayed rewards in delay discounting (DD) tasks. Human and animal data implicate ventral (amygdala, ventral striatum, ventrolateral prefrontal cortex insula) and dorsal (dorsolateral prefrontal cortex, dorsal anterior cingulate cortex and posterior parietal cortex) systems in DD decisions. The ventral system is hypothesized to respond to the salience and immediacy of rewards while the dorsal system is implicated in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
169
4
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(196 citation statements)
references
References 50 publications
22
169
4
1
Order By: Relevance
“…Although METH effects on a simple visual fMRI paradigm have not been previously reported to our knowledge, several studies of brain activation during cognitive paradigms in METH-dependent individuals have found a mixed pattern of activation, similar to that observed in MDMA users, when compared with control subjects during a facial affect matching task (Payer et al, 2008) and a delay discounting task (Monterosso et al, 2007;Hoffman et al, 2008).…”
Section: Relationship To Previous Findingssupporting
confidence: 51%
“…Although METH effects on a simple visual fMRI paradigm have not been previously reported to our knowledge, several studies of brain activation during cognitive paradigms in METH-dependent individuals have found a mixed pattern of activation, similar to that observed in MDMA users, when compared with control subjects during a facial affect matching task (Payer et al, 2008) and a delay discounting task (Monterosso et al, 2007;Hoffman et al, 2008).…”
Section: Relationship To Previous Findingssupporting
confidence: 51%
“…Thus, aberrant activation of the INS following the gambling test in METH-treated rats may reflect the response of the salience network to positive and negative RPEs in the test. Because signals related to value functions and reward prediction errors are observed in many different areas (38), many other brain areas are likely to be involved in the process of updating action value functions; consequently, impaired functions of various brain areas might contribute to more impulsive choices in METH-dependent individuals (39).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported that METH users showed increased impulsivity as measured by a delay-discounting test and showed decreased activity in the cingulate and dorsolateral PFC (Monterosso et al, 2007;Hoffman et al, 2008). Decreased activation was also observed in the frontal and insular cortices of METH users in response to a Stroop task, although task performance was not consistently different from control subjects (Salo et al, 2009;Nestor et al, 2011).…”
Section: Action Of Substituted Amphetamines and Cathinonesmentioning
confidence: 99%